CONFLICT BETWEEN TWO VILLAGES ON TELEVISION SCREEN: ANALYSIS OF THE DISCOURSE OF BALI TV COVERAGE ON KEMONING-BUDAGA CASE - Wirawan, I Komang Arba; Ardika, I Wayan Ardika; Wirawan, A.A. Bagus Wirawan (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2015)
This study is intended to analyze the discourse of Bali TV coverage on the Kemoning –Budaga case, Bali, a conflict which took place on 17 September 2011, which led to discourse of the dispersal of the traditional village ‘desa pakraman’. Such coverage of the case was considered blaming the Governor of Bali, Mangku Pastika. He was reported to intend to disperse the traditional villages in Bali. The Bali TV and Bali Post, which are under the Bali Post Media Group ‘Kelompok Media Bali Post’ (abbreviated to KMB) continuously exploited the discourse of the dispersal of the traditional village subjectively. The Governor of Bali, Mangku Made Pastika, did not accept that and prosecuted the Bali Post in Denpasar Court of First Instance ‘Pengadilan Negeri Denpasar’. The theory of discourse, the theory of agenda setting, the framing theory, and the theory of semiotics are used in the present study. The result of the analysis shows that the conflict between Kemoning Village and Budaga Village covered by the Bali Post was an extended discourse of the Bali Post printed media which was managed using a clear setting agenda for the social, political, and ideological interests of the KMB’s Ajeg Bali. The relation between the Governor of Bali, Mangku Made Pastika, and KMB, which was good in the beginning, changed into a serious conflict. It is interesting to explore the discourse of the Bali TV’s news release which aggravated the conflict in order to identify the subjective agenda of the news broadcasting policy and the counter discourse as the response to it. The main data of the present study are the discourse of the news released by the Bali TV on the Kemoning-Budaga case. The data were in the forms of the documents of the materials which were once presented. The Governor of Bali, Mangku Made Pastika, made use of the Department of the Public Relations of the Government of Bali Province and the media beyond the KMB such as the TVRI Bali and Radar Bali to present his counter discourse. The discourse on the Kemoning-Budaga Case shows a real example how the mass media do not pay attention to objectivity for the sake of power.